Innovation in Digital Game Media for Arabic Language Learning: Systematic Review and Implementable Framework - Zahra, Hana; Zakiyah, Fitri; Isa, Abdul Azim Mohamad (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2026)
The integration of digital game media in Arabic language learning has emerged as a response to declining student engagement and increasing digital distractions in the technological era. Although numerous studies report the effectiveness of Game-Based Learning (GBL), a comprehensive structural analysis of innovation patterns and implementation constraints remains limited. This study aims to systematically map digital game media innovations in Arabic language learning from 2020–2025 and to analyze how media typology, instructional design alignment, teacher readiness, and contextual conditions interact in shaping sustainable learning outcomes. Using a Systematic Literature Review (SLR) with the PRISMA protocol, 21 selected articles from Google Scholar, Scopus, and SINTA were analyzed through thematic coding and visualization using NVivo 12. The findings revealed that the effectiveness of digital game media is not determined solely by platform type, but by the systemic alignment among technological affordances, pedagogical design, educator competence, and infrastructural support. Based on these patterns, this study proposes an integrative conceptual framework that advances structural analysis beyond platform-based evaluation and supports more sustainable implementation of digital game-based Arabic language learning.